TAZ induces growth factor-independent proliferation through activation of EGFR ligand amphiregulin - Yang, Nuo (Landes Bioscience, 2012)
The Hippo signaling pathway regulates cellular proliferation and survival, thus exerting profound effects on normal cell fate and tumorigenesis. We previously showed that the pivotal effector of this pathway, YAP, is amplified in tumors and promotes epithelial-to-mesenchymal transition (EMT) and malignant transformation. Here, we report that overexpression of TAZ, a paralog of YAP, in human mammary epithelial cells promotes EMT and, in particular, some invasive structures in 3D cultures. TAZ also leads to cell migration and anchorage-independent growth in soft agar. Furthermore, we identified amphiregulin (AREG), an epidermal growth factor receptor (EGFR) ligand, as a target of TAZ. We show that AREG functions in a non-cell-autonomous manner to mediate EGF-independent growth and malignant behavior of mammary epithelial cells. In addition, ablation of TEAD binding completely abolishes the TAZ-induced phenotype. Last, analysis of breast cancer patient samples reveals a positive correlation between TAZ and AREG in vivo. In summary, TAZ-dependent secretion of AREG indicates that activation of the EGFR signaling is an important non-cell-autonomous effector of the Hippo pathway, and TAZ as well as its targets may play significant roles in breast tumorigenesis and metastasis.